MEASUREMENT AND STRATEGY TO IMPROVE THE PRODUCTIVITY OF MADURA’S PEOPLE’S SALT BUSINESS WITH OBJECTIVE MATRIX (OMAX) AND TRAFFIC LIGHT SYSTEM (CASE STUDY : PEOPLE SALT SUMENEP) - Wulandari, Aprilia; Anna, Ika Deefi; Cahyadi, Indra (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Sumenep Regency is the largest salt producing district on the island of Madura. However, the productivity of salt produced is still low. Therefore, this study aims to measure the salt productivity of the people of Sumenep, find out the factors that affect salt productivity, and provide recommendations for improvements to increase the salt productivity of the people of Sumenep. Productivity measurement uses the Objective Matrix (OMAX) method which uses 5 ratios, namely land area, salt selling price, salt farmer group, quality salt 1 and quality salt 2. The next stage is to measure the value of productivity on each criterion, determine targets and weights using the Analytical Hierarcy Process (AHP) method, determine targets and calculate OMAX levels and analyze the productivity of salt production of the people of Sumenep. The results of productivity calculations using the OMAX method showed that the highest productivity index occurred in September at 572.319%, while the lowest productivity index occurred in August at -66.727%. Based on the traffic light system method, recommendations for improvement to increase ratio 4 (quality 1) and ratio 5 (quality 2) are by making tunnels or prism houses and the use of geomembranes that can increase salt production in quantity and quality.